Ultrathin Pancharatnam–Berry Metasurface with Maximal Cross‐Polarization Efficiency. (28th December 2014) - Ding, Xumin; Monticone, Francesco; Zhang, Kuang; Zhang, Lei; Gao, Dongliang; Burokur, Shah Nawaz; de Lustrac, Andre; Wu, Qun; Qiu, Cheng‐Wei; Alù, Andrea
<x xml:space="preserve">Abstract</x> Novel ultrathin dual‐functional metalenses are proposed, fabricated, tested, and verified in the microwave regime for the first time. The significance is that their anomalous transmission efficiency almost reaches the theoretical limit of 25%, showing a remarkable improvement compared with earlier ultrathin metasurface designs with less than 5% coupling efficiency. The planar metalens proposed empowers significant reduction in thickness, versatile focusing behavior, and high transmission efficiency simultaneously. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>